Segmentation of the Electrocardiography Images as a Tool to Identify Heart Diseases - Latifah Listyalina; Dhimas Arief Dharmawan (Journal of Electrical Technology UMY, 2019)
The heart is a very vital organ. Cardiac examination can be done periodically by using an electrocardiograph. So that the heart's condition can be known. One of the optimization in helping the detection of heart disease automatically by using computer assistance. Automatic detection can be done by image processing methods as input, especially ECG images that have been segmented. In this study, ECG image segmentation is carried out through several stages, such as grayscalling, contrast enhancement, and segmentation. The hope, the results of this study can be used as input for automatic detection of heart disease.